The effect of financial literacy and user experience on e-wallet user loyalty with user satisfaction as a mediation variable on generation Z in Cirebon City - Karlina Karlina; Krisdiana Krisdiana (Universitas Nusa Cendana, 2026)
This study examines the influence of financial literacy and user experience on e-wallet user loyalty, with user satisfaction serving as a mediating variable among Generation Z in Cirebon City. Adopting a quantitative explanatory approach, data were collected from 120 active e-wallet users through a structured questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that financial literacy and user experience do not directly influence user loyalty. However, both variables have a positive and significant effect on user satisfaction, which in turn significantly enhances user loyalty. Furthermore, user satisfaction fully mediates the relationships between financial literacy and loyalty as well as between user experience and loyalty, indicating that loyalty is developed primarily through users’ satisfaction rather than through the direct effects of financial knowledge or service experience. These findings highlight the pivotal role of user satisfaction in strengthening customer retention in the digital payment ecosystem. The study contributes to the literature on digital financial services by extending understanding of the mechanisms underlying e-wallet loyalty among Generation Z and provides practical implications for service providers seeking to enhance long-term user engagement through improved customer experience and satisfaction. Keywords: Financial Literacy; User Experience; User Satisfaction; User Loyalty; E-Wallet; Generation Z